Predictors for in-flight medical interventions during helicopter interfacility transport in Hong Kong. Issue 5 (September 2022) - Cheung, Arthur Chi Kin; Lam, Rex Pui Kin; Fok, Patrick Wai Fung; Ng, Ethan Pak Hang; Chaang, Vi Ka; Rainer, Timothy Hudson
Introduction: Interfacility transport with helicopter from remote island clinics to urban hospitals account for a significant portion of the Hong Kong Government Flying Service missions. Currently, doctor and nurse escorts are deployed as volunteers only during the daytime from every Friday to Monday and on public holidays. While most transport runs smoothly, patient deterioration can occur during flight, warranting medical interventions on-board. Yet, little is known about the pattern and any clinical predictors of such interventions during helicopter interfacility transport missions. Methods: We collected Government Flying Service callout records from 1 January to 31 December 2016, and retrieved demographic, clinical and operational data. Interfacility transport mission was dispatched based on 'Casualty Evacuation' categories, which range from A+ (unstable), A (borderline) to B (stable). Univariate and multivariable logistic regression were used to identify independent predictors for in-flight medical interventions. Results: Of 1734 callout records, 386 interfacility transport missions escorted by volunteer doctors or nurses or both had complete flight medical records for analysis and 14.9% required in-flight medical interventions. Most interventions were related to oxygen therapy, intravenous fluid and administration of medications. Multivariable logistic regression showed that an age ⩾70 years, Casualty Evacuation A+ category, and any pre-flight emergency medical interventions were independent predictors for in-flight medical interventions. Conclusion: This study identified a few clinical predictors of in-flight medical interventions in an urban helicopter interfacility transport missions setting. Crewman training that focuses on the relevant procedural capabilities and clinical judgement is necessary to address the in-flight medical needs of interfacility transport missions.